An introduction to the New Testament - Brown, Raymond Edward (New York : Doubleday, 1997)
"From the experience of a lifetime of scholarship, preaching, teaching, and writing, Raymond E. Brown covers the entire scope of the New Testament with ease and clarity. He walks readers book by book through the basic content and issues of the New Testament. While a wealth of information is contained in these pages, the work's most impressive features are the basic summaries of each book, a historical overview of the ancient Greco-Roman world, discussions of key theological issues, and the rich supplementary materials, such as illustrative tables, maps, bibliographies, and appendixes. Using this basic data, Brown answers questions raised by today's readers, relates the New Testament to our modern world, and responds to controversial issues, such as those raised by the Jesus Seminar."--Jacket.
The nature and origin of the New Testament -- How to read the New Testament -- The text of the New Testament -- The political and social world of New Testament times -- The religious and philosophical world of New Testament times -- Gospels in general; synoptic gospels in particular -- The gospel according to Mark -- The gospel according to Matthew -- The gospel according to Luke -- The acts of the apostles -- The gospel according to John -- First epistle (letter) of John -- Second letter of John -- Third letter of John -- Classifications and format of New Testament letters -- General issues in Paul's life and thought -- An appreciation of Paul -- First letter to the Thessalonians -- Letter to the Galatians -- Letter to the Philippians -- Letter to Philemon -- First letter to the Corinthians -- Second letter to the Corinthians -- Letter to the Romans -- Pseudonymity and DeuteroPauline writing -- Second letter to the Thessalonians -- Letter to the Colossians -- Epistle (letter) to the Ephesians -- Pastoral letter: to Titus -- Pastoral letter: the first to Timothy -- Pastoral letter: the second to Timothy -- Letter (epistle) to the Hebrews -- First letter of Peter -- Epistle (letter) of James -- Letter (epistle) of Jude -- Second epistle (letter) of Peter -- The book of Revelation (the apocalypse) -- Appendixes : The historical Jesus; Jewish and Christian writings pertinent to the NT.
Includes bibliographical references and indexes.
Keywords: Bible. -- Introductions; Bible. -- Theology; Bible. -- Canon